2023
DOI: 10.3389/fphar.2023.1214220
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl gallate isolated from phenol-enriched fraction of Caesalpinia mimosoides Lam. Promotes cutaneous wound healing: a scientific validation through bioassay-guided fractionation

Abstract: The tender shoots of Caesalpinia mimosoides Lam. are used ethnomedically by the traditional healers of Uttara Kannada district, Karnataka (India) for the treatment of wounds. The current study was aimed at exploring phenol-enriched fraction (PEF) of crude ethanol extract of tender shoots to isolate and characterize the most active bio-constituent through bioassay-guided fractionation procedure. The successive fractionation and sub-fractionation of PEF, followed by in vitro scratch wound, antimicrobial, and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Historically, this plant has been utilized as a carminative and to heal dizziness and fainting, indicating its potential safety and capacity as a medicinal agent. C. mimosoides Lamk exhibits promising biological activities, including anticancer, antibacterial, antioxidant, anti-inflammatory, and neuroprotective effects [23][24][25][26][27][28][29]. While the virucidal effects of this plant species have not yet been investigated, previous studies revealed that C. minax and C. latisiliqua, which belong to the same genus, were rich in flavonoids, stilbene, phenolics, and other bioactive constituents and demonstrated promising antiviral activity [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, this plant has been utilized as a carminative and to heal dizziness and fainting, indicating its potential safety and capacity as a medicinal agent. C. mimosoides Lamk exhibits promising biological activities, including anticancer, antibacterial, antioxidant, anti-inflammatory, and neuroprotective effects [23][24][25][26][27][28][29]. While the virucidal effects of this plant species have not yet been investigated, previous studies revealed that C. minax and C. latisiliqua, which belong to the same genus, were rich in flavonoids, stilbene, phenolics, and other bioactive constituents and demonstrated promising antiviral activity [30,31].…”
Section: Introductionmentioning
confidence: 99%